2001
DOI: 10.1016/s0893-133x(01)00326-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Tryptophan Depletion Plus a Serotonin 1A Agonist Competing Effects on Sleep in Healthy Men

Abstract: In the present study, we hypothesized that the REMsuppressing effects of 5-HT 1A receptor stimulation would counteract the REM-disinhibiting effects of rapid tryptophan depletion (RTD), and vice versa. We administered RTD plus ipsapirone (10 mg, p.o.) The rapid tryptophan depletion (RTD) paradigm (Young et al. 1985;Delgado et al. 1990) allows researchers to study the consequences of 5-HT system deactivation. In humans and animals, RTD has been shown to cause significant (but transient) reductions in the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Previous studies have suggested that individuals with serotonergic abnormalities are more sensitive to ATD (e.g., Delgado 2006;Booij et al 2002;Moore et al 2001;Riedel et al 2002;Neumeister 2003;Neumeister et al 2006;Roiser et al 2006;Jans et al 2007). Positron emission tomography studies have found lower radioligand binding to the 5-HT transporter (a putative marker of cell integrity) in ecstasy users relative to controls (McCann et al 1998(McCann et al , 2005(McCann et al , 2008Buchert et al 2004;Thomasius et al 2006), although a recent study reported no such changes in a wellmatched sample of former users (Selvaraj et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that individuals with serotonergic abnormalities are more sensitive to ATD (e.g., Delgado 2006;Booij et al 2002;Moore et al 2001;Riedel et al 2002;Neumeister 2003;Neumeister et al 2006;Roiser et al 2006;Jans et al 2007). Positron emission tomography studies have found lower radioligand binding to the 5-HT transporter (a putative marker of cell integrity) in ecstasy users relative to controls (McCann et al 1998(McCann et al , 2005(McCann et al , 2008Buchert et al 2004;Thomasius et al 2006), although a recent study reported no such changes in a wellmatched sample of former users (Selvaraj et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep studies of 5HT 1A agonists in healthy volunteers have reported REM suppression particularly in the first 3h of sleep (Ware et al, 1994;Gillin et al, 1994;Driver et al, 1995;Seifritz et al, 1996;Moore et al, 2001). These changes appear to be modest with buspirone and more marked with ipsapirone, although there have been no direct comparison studies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some evidence even suggested opposite relationships and did not show intraindividual correlations between serotonergic REM suppression and cholinergic REM induction in depressed and healthy subjects ). In the same vein, the initially reported REM enhancing effects (Moore et al 1998) of serotonin depletion by means of a tryptophan-free amino acid challenge was not replicated in a second study carried out with virtually the same experimental parameters (Moore et al 2001).…”
Section: Discussionmentioning
confidence: 95%
“…For instance, REM sleep is suppressed following systemic 5-HT 1A agonists (Gillin et al 1994;Seifritz et al 1996) and promoted following cholinergic agonists (Sitaram et al 1976;Berger et al 1985;Gillin et al 1991b;. Muscarinic receptor antagonists, on the other hand, partially suppress REM sleep (Gillin et al 1991a), and the depletion of central serotonin enhances REM sleep Moore et al 1998Moore et al , 2001Voderholzer et al 1998). In depression, it was found that cho-S86 E. Seifritz et al N EUROPSYCHOPHARMACOLOGY 2001 -VOL .…”
Section: Aspects Of Sleep Regulationmentioning
confidence: 99%